Temperature evolution of dielectric characteristics of PVDF and P(VDF-TrFE) films produced by 4D printing - A.V. Solnyshkin; N.V. Vostrov; S.I. Gudkov; A.N. Belov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
In this work, films of polyvinylidene fluoride, copolymer of vinylidene fluoride and trifluoroethylene have been studied. The samples were made by direct ink writing technology. Some of the produced films were polarized in the corona discharge field. The dependences of the relative permittivity on temperature were studied for the films. The study showed that for polyvinylidene fluoride films, no maximum is observed in the dependences of the permittivity on temperature, since the assumed temperature of the ferroelectric phase transition is higher than the melting temperature. The maximum in the temperature dependence of permittivity for polarized copolymer of vinylidene fluoride and trifluoroethylene films is shifted by 10℃ toward higher temperatures compared to the maximum for non-polarized films. In this case, the permittivity of non-polarized films has higher values compared to the corresponding value for polarized samples. This is due to an increase in the proportion of the β-phase after polarization, as well as to the internal electric field caused by the space charge formed during the polarization process at the phase boundaries.